2003
DOI: 10.1128/jcm.41.1.509-511.2003
|View full text |Cite
|
Sign up to set email alerts
|

Clostridium difficile Brain Empyema after Prolonged Intestinal Carriage

Abstract: Clostridium difficile, the most common cause of antibiotic-associated diarrhea, is occasionally isolated from extraintestinal sites and is usually found as part of a polymicrobial flora. We report a case of brain empyema that occurred after the recurrent intestinal carriage of a nontoxigenic strain of C. difficile. Brain abscess cultures contained both toxigenic and nontoxigenic isolates. Pulsed-field gel electrophoresis showed that nontoxigenic isolates from the intestine and from the brain were identical.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…Toxinnegative strains have been isolated from monomicrobial CDI of the brain and blood. 19,20 Perhaps undefined nontoxin virulence factors are operative in extraintestinal CDI.…”
Section: Discussionmentioning
confidence: 99%
“…Toxinnegative strains have been isolated from monomicrobial CDI of the brain and blood. 19,20 Perhaps undefined nontoxin virulence factors are operative in extraintestinal CDI.…”
Section: Discussionmentioning
confidence: 99%
“…A case report from France describes a 16-year-old boy with osteosarcoma who developed a non-toxigenic C. difficile chronic septic arthritis and osteomyelitis in a prosthetic knee joint [31]. In another case, a 48-year-old man who had surgery to drain a subdural hematoma later developed a brain abscess that was infected with both non-toxigenic and toxigenic C. difficile strains [32]. Lastly, a study observing patients with diarrhea on a hematology/oncology ward found that those with non-toxigenic strains of C. difficile had a longer duration of diarrhea compared to those with a toxigenic strain [33].…”
Section: Can Non-toxigenic C Difficile Cause Disease?mentioning
confidence: 99%
“…In a recent review encompassing 59 patients with extra-intestinal C. difficile infection (CDI) (Bedimo and Weinsten 2003), three major forms of clinical manifestation were described: bacteraemia with or without focal infection (Bedimo and Weinsten 2003;Feldman et al 1995;Libby and Bearman 2009;Lee et al 2010;Gerard et al 1989;Hemminger et al 2011;Choi et al 2013), intra-abdominal infection, and extraabdominal abscesses (Bedimo and Weinsten 2003), such as a splenic abscess (Stieglbauer et al 1995;Studemeister et al 1987;Saginur et al 1983) and a brain abscess (Gravisse et al 2003). C. difficile has also been associated with reactive arthritis (Loffler et al 2004;Birnbaum et al 2008;Prati et al 2010), osteomyelitis (Al-Najjar et al 2013;Pron et al 1995;Riley and Karthigasu 1982), and prosthetic shoulder and knee joint infection (Pron et al 1995;Ranganath and Midturi 2013;McCarthy and Stingemore 1999).…”
Section: Discussionmentioning
confidence: 97%